Neodymium Isotopic Composition and Rare Earth Element Concentration Variations in the Coral and Solomon Seas - Pham, Viet Quoc; Jeandel, Catherine; Grenier, Melanie; Cravatte, Sophie; Eldin, Gerard; Belhadj, Moustafa; Germineaud, Cyril; Vu, Tu Van (Frontiers in Environmental Chemistry, 2022)
Significant progress has been made in the last decade on the understanding of the role of the Coral and Solomon Seas as major suppliers of waters and chemical elements to the equatorial Pacific. Yet, the location, depth, and processes of chemical enrichment of these waters remain poorly constrained. Neodymium (Nd) isotopic compositions (ε_Nd) and rare earth element concentrations ([REE]) are powerful tracers of land-ocean chemical exchanges. Combined, they can greatly refine the characterization of these exchanges. Here we report profiles of ε_Nd at 21 stations located in the Coral and Solomon Seas as part of the GEOTRACES GP-12 cruise that complement the rare earth element concentration ([REE]) profiles of Pham et al. (2019). Waters exiting the Solomon Sea are generally slightly more radiogenic than the incoming ones, suggesting inputs of radiogenic material along their pathways across the Solomon Sea. This radiogenic material is brought to the surface waters via natural processes (rivers, volcanic dusts) and likely local mining activities. Noticeable ε_Nd increases are also observed in subsurface and intermediate layers. All these processes indicate the occurrence of local Boundary Exchange (BE) processes, which are estimated to occur within a few days. Coupling hydrological and chemical tracers allows highlighting the land-ocean interactions affecting some water layers and quantifying the exchanged fluxes of Nd. Modifications of the Nd concentration and isotopic composition in the lower thermocline layer require an external flux of 7.9 ± 2.0 t(Nd)/yr only partly balanced by a scavenging flux of 1.8 ± 2.3 t(Nd)/yr, leading to a net influx of 6.1 ± 1.7 t(Nd)/yr. Regarding the Upper Circumpolar Deep Water, a total net flux of 105 ± 50 t(Nd)/yr is estimated, the external flux is relatively high (86 ± 31 t(Nd)/yr) while the scavenging flux remains. These results refine the role of the Solomon Sea as a supplier of continental chemical elements to the Pacific equatorial waters.